Gradient Poly(ethylene glycol) Diacrylate and Cellulose Nanocrystals Tissue Engineering Composite Scaffolds via Extrusion Bioprinting - Frost, Brody A.; Sutliff, Bradley P.; Thayer, Patrick; Bortner, Michael J.; Foster, E. Johan (Frontiers in Bioengineering and Biotechnology, 2019)
Bioprinting has advanced drastically in the last decade, leading to many new biomedical applications for tissue engineering and regenerative medicine. However, there are still a myriad of challenges to overcome, with vast amounts of research going into bioprinter technology, biomaterials, cell sources, vascularization, innervation, maturation, and complex 4D functionalization. Currently, stereolithographic bioprinting is the primary technique for polymer resin bioinks. However, it lacks the ability to print multiple cell types and multiple materials, control directionality of materials, and place fillers, cells, and other biological components in specific locations among the scaffolds. This study sought to create bioinks from a typical polymer resin, poly(ethylene glycol) diacrylate (PEGDA), for use in extrusion bioprinting to fabricate gradient scaffolds for complex tissue engineering applications. Bioinks were created by adding cellulose nanocrystals (CNCs) into the PEGDA resin at ratios from 95/5 to 60/40 w/w PEGDA/CNCs, in order to reach the viscosities needed for extrusion printing. The bioinks were cast, as well as printed into single-material and multiple-material (gradient) scaffolds using a CELLINK BIOX printer, and crosslinked using lithium phenyl-2,4,6-trimethylbenzoylphosphinate as the photoinitiator. Thermal and mechanical characterizations were performed on the bioinks and scaffolds using thermogravimetric analysis, rheology, and dynamic mechanical analysis. The 95/5 w/w composition lacked the required viscosity to print, while the 60/40 w/w composition displayed extreme brittleness after crosslinking, making both CNC compositions non-ideal. Therefore, only the bioink compositions of 90/10, 80/20, and 70/30 w/w were used to produce gradient scaffolds. The gradient scaffolds were printed successfully and embodied unique mechanical properties, utilizing the benefits of each composition to increase mechanical properties of the scaffold as a whole. The bioinks and gradient scaffolds successfully demonstrated tunability of their mechanical properties by varying CNC content within the bioink composition and the compositions used in the gradient scaffolds. Although stereolithographic bioprinting currently dominates the printing of PEGDA resins, extrusion bioprinting will allow for controlled directionality, cell placement, and increased complexity of materials and cell types, improving the reliability and functionality of the scaffolds for tissue engineering applications.